2
$\begingroup$

The probability mass function of the negative multinomial distribution is: \begin{align*} \mathbb{P}(\boldsymbol{\rm{X}}=\boldsymbol{\rm{x}}|\mathbf{p})=\frac{\Gamma\left(x_0+\sum_{i=1}^{m}x_{i}\right)}{\Gamma\left(x_0\right)}p_0^{x_0} \prod_{i=1}^{m}\frac{p_{i}^{x_i}}{x_i!}, \end{align*}

where $\mathbf{p} \equiv (p_1,...,p_m)\in\mathbb R_+^m$ and $p_0 \equiv 1-\sum_{i=1}^m p_i$. Taking $x_0$ to be fixed as the number of successful draws from the "first" group, the mean vector and variance matrix of the distribution of the remaining $m$ values are given respectively by:

\begin{align*} \boldsymbol{\rm{\mu}}=\frac{x_0}{p_{0}}\boldsymbol{\rm{p}} \quad \quad \quad \quad \quad {\boldsymbol {\Sigma }}=\frac{x_0}{p_{0}^{2}}\boldsymbol{\rm{p}}\boldsymbol{\rm{p'}}+\frac{x_0}{p_{0}}{\rm{diag}(\boldsymbol{\rm{p}})}. \end{align*}

I want to show that the determinant of the variance matrix is:

\begin{align*} {\displaystyle |{\boldsymbol {\Sigma }}|={\frac {1}{p_{0}}}\prod _{i=1}^{m}{\mu _{i}}}, \end{align*}

where the values in the product are elements of the mean vector. How can I derive this result?

$\endgroup$
2
  • $\begingroup$ There is this equation on Wikipedia(en.m.wikipedia.org/wiki/Negative_multinomial_distribution), but I don't know how they got it $\endgroup$
    – d d
    Jun 3, 2022 at 9:47
  • $\begingroup$ It's crucial to specify that $p_0 = 1 - (p_1+\cdots+p_m),$ for otherwise this result is not generally true. One way to derive it is via row reduction to relate the case $m$ to the case $m-1,$ then proceed inductively. $\endgroup$
    – whuber
    Jun 3, 2022 at 13:37

1 Answer 1

3
$\begingroup$

As a preliminary step, we note the result of the following quadratic form:

$$\mathbf{p}' \text{diag} (\mathbf{p})^{-1} \mathbf{p} = \mathbf{p}' \mathbf{1} = \sum_{i=1}^m p_i = 1-p_0.$$

Now, using the matrix determinant lemma, we have:

$$\begin{align} |\boldsymbol{\Sigma}| &= \bigg| \frac{x_0}{p_{0}^{2}} \mathbf{p} \mathbf{p}' + \frac{x_0}{p_{0}}\text{diag} (\mathbf{p}) \bigg| \\[6pt] &= \bigg( 1 + \frac{\mathbf{p}' \text{diag} ( \mathbf{p})^{-1} \mathbf{p}}{p_0} \bigg) \bigg| \frac{x_0}{p_{0}} \text{diag} (\mathbf{p}) \bigg| \\[6pt] &= \bigg( 1 + \frac{1-p_0}{p_0} \bigg) \prod_{i=1}^m \frac{x_0}{p_0} p_i \\[6pt] &= \frac{1}{p_0} \prod_{i=1}^m \frac{x_0}{p_0} p_i \\[6pt] &= \frac{1}{p_0} \prod_{i=1}^m \mu_i. \\[6pt] \end{align}$$

As you can see, the result you are interested in is a direct result of the matrix determinant lemma; if you are interested in a proof of the latter you can find it here.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.